PENILAIAN KINERJA KEPALA SEKOLAH - ABBAS, ABBAS (DIDAKTIKA, 2017)
This journal discusses about the performance of the principal. Assessment is a systematic effort of collecting, organizing, managing and interpreting data, facts and information (which can be accounted for) with the aim of concluding the value or rating of one's competence in one type or area of expertise of the educational personality such as the principal. The performance of the principal is the work done by the principal in carrying out the main tasks, functions and responsibilities in managing the school he or she is in. Procedures to be passed in the performance appraisal are working procedures and work steps since the process of understanding the performance starts from composing instruments and piloting, collecting data, analyzing data and preparing reports. The results of the principal's performance appraisal are used to improve the professionalism of the principal.